Ultrahigh‐Power‐Factor Carbon Nanotubes and an Ingenious Strategy for Thermoelectric Performance Evaluation. Issue 25 (19th May 2016) - Zhou, Wenbin; Fan, Qingxia; Zhang, Qiang; Li, Kewei; Cai, Le; Gu, Xiaogang; Yang, Feng; Zhang, Nan; Xiao, Zhuojian; Chen, Huiliang; Xiao, Shiqi; Wang, Yanchun; et al.
Abstract : An ingenious strategy is put forward to evaluate accurately the thermoelectric performance of carbon nanotube (CNT) thin films, including thermal conductivity, electrical conductivity, and Seebeck coefficient in the same direction. The results reveal that the as‐prepared CNT interconnected films and CNT fibers possess enormous potential of thermoelectric applications because of their ultrahigh power factors.